Decoding the interplay of medical professionalism, mental well-being, and coping in undergraduate medical students across culture: using structural equation modeling - Sattar, Kamran; Meo, Sultan Ayoub; Yusoff, Muhamad Saiful Bahri (Frontiers in Medicine, 2024)
The rigorous nature of medical education, long and night shifts, and prevalent issues like stress, anxiety, and depression affect medical students' mental well-being and medical professionalism. This study aims to explore the intricate relationships between mental well-being, medical professionalism, and coping strategies, among undergraduate medical students, utilizing Structural Equation Modelling (SEM) to unravel these dynamics. Methods: Conducted at Universiti Sains Malaysia, this cross-sectional study involved 234 medical students from the 1st, 3rd, and 5th years of the MBBS program. Data were collected via five validated survey instruments: DASS-9, TEQ, Dundee, Brief COPE, and CBI, through Google Forms. Participants were selected using purposive sampling. The surveys assessed mental well-being (burnout, anxiety, depression, stress), coping strategies, and medical professionalism attributes. Model fit was evaluated using established indices. Results: Findings indicated that professional behavior reduces burnout and negatively impacts negative coping strategies (NCSs). Additionally, medical professionalism indirectly enhances empathy and positively influences CSs. Conversely, psychological distress increases NCSs and reduces empathy. Positive coping strategies (PCSs) enhance empathy levels, while MWB issues elevate NCSs. Discussion: The study underscores the vital role of professional behavior in mitigating burnout and fostering positive coping mechanisms among medical students. Addressing MWB issues through targeted interventions can enhance empathy and professional behavior, ultimately improving the quality of patient care.